2020
DOI: 10.1192/bjp.2020.9
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of the International Trauma Questionnaire to assess post-traumatic stress disorder in treatment-seeking veterans

Abstract: BackgroundVeterans with post-traumatic stress disorder (PTSD) typically report a poorer treatment response than those who have not served in the Armed Forces. A possible explanation is that veterans often present with complex symptoms of PTSD. ICD-11 PTSD and complex PTSD (CPTSD) have not previously been explored in a military sample.AimsThis study aimed to validate the only measure of ICD-11 PTSD and CPTSD, the International Trauma Questionnaire, and assess the rates of the disorder in a sample of treatment-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 27 publications
11
46
1
3
Order By: Relevance
“…Previous studies (Ho et al, 2020;Karatzias et al, 2017;Murphy et al, 2020; have shown that the latent structure of the ITQ is best represented by two models: a) A correlated six-factor model distinguishing between clusters of symptoms and b) a two-factor second-order model where the correlations between symptom clusters are explained by two second-order factors reflecting PTSD and DSO. Results from previous studies suggest that the second-order model has a better fit in clinical and highly trauma-exposed samples in studies that have used the ITQ (Cloitre et al, 2018;Karatzias et al, 2017;Møller et al, 2019;Vallières et al, 2018), and in studies using other measures for the PTSD and DSO constructs Nickerson et al, 2016;Tay, Rees, Chen, Kareth, & Silove, 2015), whereas the first-order model has displayed a better fit in general population and non-clinical samples studies using the ITQ (Ben-Ezra et al, 2018;Ho et al, 2020;Shevlin et al, 2017).…”
Section: Internal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Ho et al, 2020;Karatzias et al, 2017;Murphy et al, 2020; have shown that the latent structure of the ITQ is best represented by two models: a) A correlated six-factor model distinguishing between clusters of symptoms and b) a two-factor second-order model where the correlations between symptom clusters are explained by two second-order factors reflecting PTSD and DSO. Results from previous studies suggest that the second-order model has a better fit in clinical and highly trauma-exposed samples in studies that have used the ITQ (Cloitre et al, 2018;Karatzias et al, 2017;Møller et al, 2019;Vallières et al, 2018), and in studies using other measures for the PTSD and DSO constructs Nickerson et al, 2016;Tay, Rees, Chen, Kareth, & Silove, 2015), whereas the first-order model has displayed a better fit in general population and non-clinical samples studies using the ITQ (Ben-Ezra et al, 2018;Ho et al, 2020;Shevlin et al, 2017).…”
Section: Internal Structurementioning
confidence: 99%
“…The ITQ includes six items to assess symptoms of PTSD and six items that assess symptoms of DSO and additional items assessing functional impairment related to PTSD and DSO separately. The ITQ is the only existing self-report measure that enables assessment of both ICD-11 PTSD and DSO (Cloitre et al, 2018) and has been validated internationally with studies conducted in Europe (Karatzias et al, 2017;Murphy et al, 2020), the Middle East (Gilbar, Hyland, Cloitre, & Dekel, 2018;Vallières et al, 2018), Asia (Ho et al, 2020;Mordeno, Nalipay, & Mordeno, 2019), Africa (Owczarek et al, 2019), and North America (Cloitre et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, one study has examined CPTSD with treatment-seeking military service members or veterans. Focusing on 177 veterans from the United Kingdom (UK) who pursued mental health treatment in the recent past, Murphy et al (2020b) (2020a) documented veterans with probable CPTSD had higher overall scores than those with or without PTSD. In combination, findings indicate CPTSD might be more prevalent than PTSD among treatment-seeking veterans and MI-related problems could be particularly relevant among veterans with complex emotional responses to their traumas that warrant a diagnosis of CPTSD.…”
Section: Clinical Impact Statementmentioning
confidence: 99%
“…Although the validity of CPTSD as a clinical syndrome has been questioned (Herman, 2012;Resick et al, 2012), primarily owing to overlapping symptomology with other trauma-related disorders (Wolf et al, 2015), there is now a significant body of literature that supports the hierarchical structure presented in the ICD-11. This includes a notable systematic review (Brewin et al, 2017) and a variety of validation studies: latent class analyses (Barbieri et al, 2019;Ho et al, 2020;Hyland et al, 2018;Jowett, Karatzias, Shevlin, & Albert, 2019;Karatzias et al, 2017), confirmatory factor analyses Karatzias et al, 2016;Kazlauskas, Gegieckaite, Hyland, Zelviene, & Cloitre, 2018;Murphy et al, 2020;Owczarek et al, 2020), and network analyses (Gilbar, 2020;Knefel et al, 2019Knefel et al, , 2020Knefel, Tran, & Lueger-Schuster, 2016;McElroy et al, 2019). These studies have used the only standardized self-report measure for symptoms of ICD-11 PTSD and CPTSD, the International Trauma Questionnaire (ITQ; Cloitre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%